Recurrent cardiac rhabdomyosarcoma with multiple metastases: A case report: Recurrent cardiac rhabdomyosarcoma - Reyhanoglu , Hasan; Edem , Efe; Ozcan , Kaan; Altınok , Tayfun (Journal of Surgery and Medicine, 2022)
Rhabdomyosarcoma, which accounts for 20% of all malignant tumors of the heart, is an aggressive tumor originating in the ventricular wall. These tumors are the second most common malignant primary tumor of the heart after angiosarcoma. Despite treatment options, such as surgical resection, radiotherapy, and chemotherapy, recurrence is common and mortality is high. Among these patients, survival with surgical resection is around six months to one year. In this case report, we discuss a patient who presented with recurrent rhabdomyosarcoma with distant metastasis after surgical intervention. A 56-year-old male patient who underwent left atrial mass excision and mitral valve replacement ten months prior was admitted with recurrent metastatic rhabdomyosarcoma.